THE IMPLEMENTATION OF LINK 16 IN THE POLISH ARMED FORCES AND ITS INFLUENCE ON DEFENCE CAPABILITIES, NATIONAL SECURITY AND IMAGE OF POLAND AS A NATO MEMBER - ORZOŁ Andrzej (2015)
The article shows the history and origins of Tactical Data Systems, their structure and purposes in countries who are members of North Atlantic Treaty Organization with the emphasis on LINK 16 standard. It describes the epect of LINK 16 implementation in the Polish Armed Forces on Poland’s interoperability as a fully – uedged NATO member thus increasing defense capabilities, national security and enhancing the Polish Armed Forces’ image in the international arena. What is more, typical examples of Tactical Data Links operations during military exercises, in peacetime and while trying to solve geopolitical, military conuicts in the world have also been characterized.